Erzählte Rahmen: Realismus als Problem - Öhlschläger, Claudia (Rahmenbrüche, Rahmenwechsel)

Amor sacro e profano: Modelle und Modellierungen himmlischer und irdischer Liebe in Literatur und Malerei der italienischen Renaissance - Steigerwald, Jörn (‚Amor sacro e profano': Modelle und Modellierungen der Liebe in Literatur und Malerei der italienischen Renaissance)

Amor cortigiano. Die Modellierung höfischer Liebe im rinascimentalen Epos (am Beispiel von Ariostos „Orlando furioso“) - Steigerwald, Jörn (‚Amor sacro e profano’: Modelle und Modellierungen der Liebe in Literatur und Malerei der italienischen Renaissance)

Humorism: Literary Insights in Modern Times, According to Luigi Pirandello („L’Umorismo“, „Uno, nessuno e centomila“)2003 - Steigerwald, Jörn (Aisthesis und Noesis. Zwei Erkenntnis-Formen vom 18. Jahrhundert bis zur Gegenwart)

Erschriebene Bilder: Giovanni Boccaccios „Amorosa visione“ - Steigerwald, Jörn (Poiesis. Praktiken der Kreativität in den Künsten der Frühen Neuzeit)

De la querelle entre l'Arioste et le Tasse à la dispute entre l'ésthétique de l'Arioste et du Tasse. In: La dispute entre l'Arioste et le Tasse : Les appropriations de deux esthétiques antagonistes au XVIIe siècle en France - Steigerwald, Jörn; Roussillon, Marine (Papers on French Seventeenth Century Literatur XL, 79)

Himmlische Klänge: Die Paradiso-Cantica in Dantes „Divina Commedia“ - Steigerwald, Jörn; Ackermann , Christiane; Bleumer, Hartmut (LILI 171 (2013), Gestimmte Texte)

Äffische Nachahmung: Pietro Aretinos „Sei giornate“ - Steigerwald, Jörn (Wolfenbütteler Renaissance- Mitteilungen 34/1, 2012/2013)

De la comédie érudite à la comédie de salon: Les appropriations de l'Arioste par Molière („L'école des maris“, „L'école des femmes“, „La critique de l'école des femmes“). In: La dispute entre l'Arioste et le Tasse : Les appropriations de deux esthétiques antagonistes au XVIIe siècle en France - Steigerwald, Jörn; Roussillon, Marine (Papers on French Seventeenth Century Literature Literatur XL, 79)

La querelle des „Suppositi“ de l’Arioste - Steigerwald, Jörn (Littératures classiques 81, 2013, Le temps des Querelles, sous la direction de Jeanne-Marie Hostiou / Alain Viala)

Selbstbeurteilung. Fördermagazin Sekundarstufe Deutsch. Heft 4/2013

„Ich kann mich doch nicht selbst beurteilen…“ – Wege zur Selbstbeurteilung im Deutschunterricht. Basisbeitrag - Rezat, Sara (Fördermagazin Sekundarstufe 4/2013)

„Dann heiße ich doch lieber Pflaume!“. Mehrsprachige Literatur im Sprachförderunterricht - Zierau, Cornelia; Kofer, Martina (Chancen der Vielfalt nutzen lernen. Modellprojekt. (= http://www.kommunale-integrationszentren-nrw.de/sites/default/files/public/system/downloads/chancen_der_vielfalt_buch_internetversion_0.pdf))

„F. ist in einem Labyrint [sic!], er wird wohl kaum mehr herauskommen.“ – Mythologische und alttestamentarische Metaphern des Scheiterns in den Texten Franz Kafkas, Friedrich Dürrenmatts und Jorge Luis Borgesʼ - Famula, Marta (Kafka interkulturell. Forschungen der Deutschen Kafka-Gesellschaft)

Narrative Grenzgänger – Identitätskonstruktionen in zeitgenössischer Adoleszenz-Prosa. Annette Pehnts Insel 34 und Harald Grills gehen lernen - Famula, Marta (Corpora und Canones. Schlesien und andere Räume in Sprache, Literatur und Wissenschaft)

Erlebtes, Erkanntes und Fingiertes. Dürrenmatts ästhetisches Konzept der Epistemologie in seinem autobiographischen Projekt Stoffe I-IX - Famula, Marta (Auto(r)fiktion. Literarische Verfahren der Selbstkonstruktion)

Tribo-Dynamical Analysis of Cylindrical Worm Gear Drives - Magyar, Balázs; Sauer, B; Horák, P (VDI Berichte 2199)

Temperaturberechnung im RWDR-Dichtkontakt - Magyar, Balázs; Frölich, D; Sauer, B

Contact Modeling of Rough Surfaces - Magyar, Balázs; Sauer, B

Marte Meo als Supervisionsmethode: Eine Untersuchung über die Erfahrungen von Mitarbeitern und Mitarbeiterinnen einer Kindertagesstätte - Wächter, I.; Laubenstein, Désirée (In: Zeitschrift für Heilpädagogik, 64. Jahrgang, Nr. 4,)

Exploring reasons and consequences of academic procrastination: An interview study - Grunschel, Carola; Patrzek, Justine; Fries, Stefan (European Journal of Psychology of Education)

Exploring different types of academic delayers: A latent profile analysis - Grunschel, Carola; Patrzek, Justine; Fries, Stefan (Learning and Individual Differences)

Procrastination - Klingsieck, Katrin B. (European Psychologist)
Procrastination is a well-known phenomenon that often entails negative outcomes with regard to performance and subjective well-being. In an attempt to understand the (alarming) character of procrastination, a large body of research on the causes, correlates, and consequences of procrastination has been accumulating over the last 40 years. The aim of this paper is to provide a systematic characterization of the trends in procrastination research and to suggest future directions for research and practice. The systematic characterization comprises a comparison of procrastination to functional forms of delay (referred to as strategic delay) and a presentation of the theoretical approaches to explaining procrastination. The future directions suggested pertain to the development of a differentiated understanding of procrastination and of integral interventions.

Why Students Procrastinate: A Qualitative Approach - Klingsieck, Katrin B.; Grund, Axel; Schmid, Sebastian; Fries, Stefan (Journal of College Student Development)

Procrastination in Different Life-Domains: Is Procrastination Domain Specific? - Klingsieck, Katrin B. (Current Psychology)

Employability und Prokrastination aus einer hochschuldidaktischen Perspektive - Gerholz, Karl-Heinz; Klingsieck, Katrin B. (Das Hochschulwesen)

Kleine Wörter

Kleine Wörter - große Wirkung. Text schreiben mit "und", "trotzdem" und "weil" - Topalovic, Elvira; Tophinke, Doris; Uhl, Benjamin (Praxis Deutsch)

Kleine Wörter (Basisartikel) - Tophinke, Doris (Praxis Deutsch)

External governance outcome and microfinance success - Uhde, André; Müller, Oliver (International Journal of Monetary Economics and Finance)
Employing a Hausman–Taylor instrument variable (HT–IV) estimator to data from 558 microfinance institutions (MFIs) in 80 developing countries for the period from 2002 to 2007, this paper provides empirical evidence for a positive impact of a country's external governance quality and outcome on local microbanks' economic success in terms of profitability and sustainability. Evidence as well suggests a negative relationship between external governance and the microbanks' social success measured by the depth of outreach. In this context, our analysis reveals that a country's political stability, governance effectiveness, regulatory quality and rule of law are significant key elements of external governance affecting the MFIs' functional performance. Moreover, results from sensitivity analyses indicate that the relationship between external governance quality and microfinance functional performance significantly depends on the microbanks' business concepts, their lending methodologies and sources of funding.
Keywords: microfinance; external governance; economic success; social success; developing countries; profitability; sustainability; microbanks; outreach; political stability; governance effectiveness; regulatory quality; rule of law; governance quality; lending methodologies; funding sources

The light and dark side of TARP - Farruggio, Christian; Michalak, Tobias C.; Uhde, André (Journal of Banking and Finance)
Employing four event dates of the U.S. “Troubled Asset Relief Program” (TARP) this paper empirically investigates the impact of the first announcement of TARP (September 19, 2008), the announcement of revised TARP (October 14, 2008), respective capital infusions under TARP-CPP and capital repayments on changes in shareholder value and risk exposure of 125 supported U.S. banks as perceived by the capital market through share price reactions for an entire sample period from September 19, 2008 to June 16, 2010. Our analysis reveals a light and a dark side of TARP. While announcements as well as capital repayments may restore market confidence and financial stability, equity capital injections to banks are observed to be a severe impediment to an increase in bank shareholder value and financial soundness.
Keywords: Financial crisis; TARP; Market efficiency; Event study

Sprachliche Muster in der mittelniederdeutschen Rechtssprache. Zum Sachsenspiegel und zu Stadtrechtsaufzeichnungen des 13. bis 16. Jahrhunderts - Wallmeier, Nadine

Für eine veränderte Fachpraxis - Zur Kultur und Technik der Nahrungszubereitung und Mahlzeitengestaltung - Schlegel-Matthies, Kirsten; Methfessel, Barbara (Haushalt in Bidlung und Forschung)

Der Wendenkreuzzug - Kamp, Hermann (Schwertmission. Gewalt und Christianisierung im Mittelalter)

Gewalt und Mission: Die Elb- und Ostseeslawen im Fadenkreuz des Reiches und der Sachsen vom 10. bis zum 12. Jahrhundert - Kamp, Hermann (Credo. Die Christianisierung Europas im Mittelalter)

Schwertmission. Gewalt und Christianisierung im Mittelalter

Korrekturen in sprachlichen Fächern - Hohwiller, Peter

Zur Handlungsvalidität von Tests zum professionellen Wissen von Lehrkräften - Vogelsang, Christoph; Reinhold, Peter (Zeitschrift für Didaktik der Naturwissenschaften)

Vorratsbomben im Himmel. Über digitalen Terror, unsichtbare Opfer und die Rhetorik der Präzision - Weber, Jutta (Heinrich-Böll-Stiftung: High-Tech-Kriege: Frieden und Sicherheit in Zeiten von Drohnen, Kampfrobotern und digitaler Kriegsführung)

Automatisierte Verantwortungslosigkeit? Kampfdrohnen als Mittel der High-Tech-Kriegsführung - Weber, Jutta (FIfF Kommunikation 1/2013)

Efficient Power-Intent Validation Using "Loosely-Timed" Simulation Models: A Non-Invasive Approach - Mischkalla, Fabian; Müller, Wolfgang
Faced with increasing demands on energy efficiency, current electronic systems operate according to complex power management schemes including more and more fine-grained voltage frequency scaling and power shutdown scenarios. Consequently, validation of the power design intent should begin as early as possible at electronic system-level (ESL) together with first executable system specifications for integrity tests. However, today's system-level design methodologies usually focus on the abstraction of digital logic and time, so that typical low-power aspects cannot be considered so far. In this paper, we present a high-level modeling approach on top of the SystemC/TLM standard to simulate power distribution and voltage based implications in a "loosely-timed" functional execution context. The approach reuses legacy TLM models and prevents the need for detailed lock-step process synchronization in contrast to existing methods. A case study derived from an open source low-power design demonstrates the efficiency of our approach in terms of simulation performance and testability.
Keywords: Time-varying systems; Time-domain analysis; Synchronization; Context modeling; Clocks; Semantics; Standards

An Energy-Efficient Heuristic for Hard Real-Time System on Multi-Core Processors - He, Da; Müller, Wolfgang (Proceedings of the International Conference on Applied Computing (AC))
In the electronic system development, energy consumption is clearly becoming one of the most important design concerns. From the system level point of view, Dynamic Power Management (DPM) and Dynamic Voltage and Frequency Scaling (DVFS) are two mostly applied techniques to adjust the tradeoff between the performance and power dissipation at runtime. In this paper, we study the problem of combined application of both techniques with regard to hard real-time systems running on cluster-based multi-core processors. To optimize the processor energy consumption, a heuristic based on simulated annealing with efficient termination criterion is proposed. The experiment results show that the proposed algorithm outperforms the existing approaches in terms of the energy reduction.
Keywords: Dynamic Power Management; Dynamic Voltage and Frequency Scaling; Hard Real-Time; Multi-core Processor

Does Financial Statement Audit Reduce the Cost of Debt of Private Firms? - Kosi, Urska; Koren, Jerney; Valentincic, Aljosa
This study examines the effect of audit on private firms’ cost of debt. We use a sample of 1,949 small private firms operating in the period 2006-2010 with optional financial statement audit. High quality data allows us to construct a more precise interest rate measure than existing studies employ. After controlling for obvious sources of demand for voluntary audits (ownership complexity, subsidiary status, bank relations), we find a robust central result that voluntary audits increase rather than decrease the cost of debt financing, contrary to several existing studies. This finding indicates that voluntary audits are generally treated as “adopting a label” and penalised by creditors, regardless of the perceived auditor quality as a result of the lemon problem in the audit market. Even Big-4 audits increase the cost of debt, likely as a result due to the lemon problem in the audit market, although the increase is smaller than for non-Big-4 audits. The results are sensitive to the estimation method used (OLS, Heckman’s two-step, PSM) and (sub-)sample selection. We show that disregarding the underlying assumptions of these estimation methods may lead to incorrect inferences. Additional analyses show that audited firms’ reported earnings are less informative about future operating performance than earnings of their unaudited counterparts. Our results also indicate that results are sensitive to cost of debt definition and this might have affected the results reported in the existing literature.
Keywords: private firms; voluntary audit; cost of debt; self-selection bias; lemon problem

Does Mandatory IFRS Adoption Improve the Credit Relevance of Accounting Information? - Kosi, Urska; Florou, Annita; Pope, Peter F.

Positive Beispiele zu negativen Zahlen – Unterrichtsstudien zum~Mathematikunterricht. Verlängerungsantrag zum Forschungs- und Entwicklungsplan 2013–2015 - Althoff, Paula G.; Friedli, Reto; Hattermann, Mathias; Vom Hofe, Rudolf; Kullmann, Harry; Lukas, Janine; Viehmeister, Frauke (Laborschulforschung 2013. Anträge und Berichte zum forschungs- und Entwicklungsplan. Werkstattheft Nr. 48)

Learning by Doing – Improving Academic Skills - Temmen, Katrin; Walther, Thomas (International Journal of Engineering Pedagogy (iJEP))
Engineering faculties generally involve their students in the creation of numerous scientific works and publications. However, students are rarely trained in this area and could well benefit from targeted support: to this end, we propose a specific lecture that addresses the subtleties of scientific research and writing and allows the students to apply and mentally anchor their acquired knowledge while composing a basic scientific term paper.
Keywords: General Engineering; Education

'Learning by doing' Improving academic skills - Temmen, Katrin; Walther, T. (2013 IEEE Global Engineering Education Conference (EDUCON))

Auf die Studierenden hören: Einsatz von Schülerlaboren in der Lehramtsausbildung - Temmen, Katrin (Didaktik im Fokus)

Lehrerbildung praxisorientiert gestalten - Das Projekt InnoTrans Uni-BK - Gerholz, K.-H.; Bödeker, J.; Eberhardt, A.; Kerstingtombroke, D.; Langeleh, D.; Temmen, Katrin (Wirtschaft und Erziehung)

Identifying and Tackling Inequality: A Challenge for Social Work - Dahmen, Stephan; Beuret, Benoit; Bonvin, Jean-Michel (Schweizerische Zeitschrift für Soziale Arbeit/Revue suisse de travail social)

Experimental Observation of the Spectral Gap in Microwave n-Disk Systems - Barkhofen, Sonja; Weich, Tobias; Potzuweit, A.; Stöckmann, H.-J.; Kuhl, U.; Zworski, M. (Physical Review Letters)
Keywords: General Physics and Astronomy

Bach (Familie) - Grotjahn, Rebecca (Lexikon der Kirchenmusik Bd. 2)

Kantate - Grotjahn, Rebecca (Lexikon der Kirchenmusik Bd. 2)

Analyse und Synthese elastokinematisch optimierter Verbundlenkerachsen - Entwicklung einer Verbundlenkerachse mit entkoppeltem Radträger - Schultz, Erik
Das Marktportfolio der Hinterachsen weist zwischen den Achskonzepten Schwertlenkerachse und Verbundlenkerachse sowohl im Bereich der fahrdynamischen Auslegungsmöglichkeiten als auch unter Kosten- und Gewichtsaspekten eine Lücke auf. Dieser vom Markt zur Zeit nicht gedeckte Bereich lässt sich durch eine gezielte elastokinematische Aufwertung von Verbundlenkerachsen schließen. Zur Aufwertung und Weiterentwicklung der Verbundlenkerachse ist eine elastokinematische Spurkorrektur unter Seitenkraft und unter Bremskraft sowie eine Verbesserung des Verhältnisses zwischen Seiten- und Längssteifigkeit notwendig. Die vorliegende Promotionsschrift beschreibt und analysiert zunächst die Eigenschaften bestehender Ansätze zur elastokinematischen Optimierung von Verbundlenkerachsen. Basierend auf den Erkenntnissen dieser Untersuchungen wird eine Verbundlenkerachse mit entkoppeltem Radträger entwickelt, welche sowohl unter wirtschaftlichen als auch unter performanten Gesichtspunkten zwischen einer regulären Verbundlenkerachse und einer Schwertlenkerachse platziert werden kann. Die Entwicklung erfolgt vom Konzeptentwurf bis zum auskonstruierten Bauteil auf Basis numerischer Simulation. Die entwickelte Konstruktion wird in einen Prototypen überführt, welcher in einen Ford Focus implementiert wird. In Fahr- und Komponentenversuchen wird das Verhalten des neuen Achskonzepts untersucht und mit konkurrierenden Achskonzepten verglichen.
Keywords: Verbundlenkerachse; Fahrwerk; Hinterachse; Elastokinematik; entkoppelter Radträger

Frauen in der Kirchenmusik - Grotjahn, Rebecca (Lexikon der Kirchenmusik Bd. 2)

Ernährung- und Konsumbildung - Bigga, Regine (Haushalt in Bildung und Forschung)

Übernahme von Regionalismen durch Zugezogene - Lorenz, Cornelia (Akten des XII. Internationalen Germanistenkongresses Warschau 2010 „Vielheit und Einheit der Germanistik weltweit“)

Niederdeutsche Lexeme im Regiolekt – eine empirische Studie unter Einheimischen und Zugezogenen in Ostwestfalen - Lorenz, Cornelia (Quaderni di Palazzo Serra 22)

Perspectives on Mobility

Electrical and optical properties of TiO2thin films prepared by plasma-enhanced atomic layer deposition - Dang, Van-Son; Parala, Harish; Kim, Jin Hyun; Xu, Ke; Srinivasan, Nagendra B.; Edengeiser, Eugen; Havenith, Martina; Wieck, Andreas D.; de los Arcos de Pedro, Maria Teresa; Fischer, Roland. A.; Devi, Anjana (physica status solidi (a))

MOCVD of tungsten nitride thin films: Comparison of precursor performance and film characteristics - Srinivasan, Nagendra B.; Thiede, Tobias B.; de los Arcos de Pedro, Maria Teresa; Rogalla, Detlef; Becker, Hans-Werner; Devi, Anjana; Fischer, Roland A. (physica status solidi (a))

Atomic layer deposition of Er2O3 thin films from Er tris-guanidinate and water: process optimization, film analysis and electrical properties - Xu, Ke; Chaudhuri, Ayan Roy; Parala, Harish; Schwendt, Dominik; de los Arcos de Pedro, Maria Teresa; Osten, H. Jörg; Devi, Anjana (Journal of Materials Chemistry C)

Transition metal nitride thin films grown by MOCVD using amidinato based complexes [M(NtBu)2{(iPrN)2CMe}2] (M=Mo, W) as precursors - Srinivasan, N.B.; Thiede, T.B.; de los Arcos de Pedro, Maria Teresa; Gwildies, V.; Krasnopolski, M.; Becker, H.-W.; Rogalla, D.; Devi, A.; Fischer, R.A. (Surface and Coatings Technology)

Target implantation and redeposition processes during high-power impulse magnetron sputtering of aluminum - Will, Andreas; de los Arcos de Pedro, Maria Teresa; Corbella, Carles; Hecimovic, Ante; Machura, Patrick D; Winter, Jörg; von Keudell, Achim (Journal of Physics D: Applied Physics)

Particle beam experiments for the analysis of reactive sputtering processes in metals and polymer surfaces - Corbella, Carles; Grosse-Kreul, Simon; Kreiter, Oliver; de los Arcos de Pedro, Maria Teresa; Benedikt, Jan; von Keudell, Achim (Review of Scientific Instruments)

Instabilities in high-power impulse magnetron plasmas: from stochasticity to periodicity - Winter, J; Hecimovic, A; de los Arcos de Pedro, Maria Teresa; Böke, M; Schulz-von der Gathen, V (Journal of Physics D: Applied Physics)

Insight into the Reaction Scheme of SiO2 Film Deposition at Atmospheric Pressure - Rügner, Katja; Reuter, Rüdiger; Ellerweg, Dirk; de los Arcos de Pedro, Maria Teresa; von Keudell, Achim; Benedikt, Jan (Plasma Processes and Polymers)

Abstimmung in Bewegung. Intersubjektivität im Tango Argentino - Haller, Melanie

(Erzählte) Zeit des Wartens. Semantiken und Narrative eines temporalen Phänomens. - Benz, Nadine

Inszenierungen eines Affekts: Scham und ihre Konstruktion in der Literatur der Moderne - Heidgen, Michael

Write-offs and profitability in private firms: Disentangling the impact of tax-minimisation incentives - Kosi, Urska; Valentincic, Aljosa (European Accounting Review)
Private firms are likely to use the financial reporting process more for other objectives, such as tax savings, than for communicating performance. However, observing firms choosing accounting policies for tax-minimisation purposes is not straightforward due to (i) tax and non-tax costs of reporting lower income (ii) accounting policies that result in lower reported income and no tax savings but generate non-tax benefits (iii) preparers' multiple incentives and (iv) econometric issues. We observe a large sample of 20,505 private firms writing off assets in two separate regimes, one that generates tax savings and one that does not. Firms significantly decrease, but continue to use, write-offs after the adverse change in tax treatment of write-offs. The exogenous tax change should not affect other reporting incentives. This allows us to disentangle the tax-minimisation incentive from other (un-observable) incentives, including debt contracting, dividends and employee relations that contribute to the observed anomalous positive relationship between write-offs and profitability. We show that for private firms (i) obtaining tax savings is important overall (ii) non-tax costs and benefits are probably also important and (iii) earnings informativeness for future cash flows increases after the adverse tax legislation change.

Does mandatory IFRS adoption facilitate debt financing? - Florou, Annita; Kosi, Urska

X-ray scattering of nematic liquid crystal nanodispersion with negative dielectric anisotropy [Invited] - Lorenz, Alexander; Zimmermann, Natalie; Kumar, Satyendra; Evans, Dean R.; Cook, Gary; Martínez, Manuel Fernández; Kitzerow, Heinz-Siegfried (Applied Optics)
Keywords: Atomic and Molecular Physics; and Optics; Engineering (miscellaneous); Electrical and Electronic Engineering

Hysteresis and memory factor of the Kerr effect in blue phases - Nordendorf, Gaby; Lorenz, Alexander; Hoischen, Andreas; Schmidtke, Jürgen; Kitzerow, Heinz-Siegfried; Wilkes, David; Wittek, Michael (Journal of Applied Physics)
Keywords: General Physics and Astronomy

Liquid crystal lasers: recent advances - Schmidtke, Juergen; Lu, Lu; Kitzerow, Heinz-Siegfried; Terentjev, Eugene M. (SPIE Proceedings)

First Endless Optical Polarization and Phase Tracker - Koch, B.; Noé, Reinhold; Mirvoda, V.; Sandel, D. (2013 OPTICAL FIBER COMMUNICATION CONFERENCE AND EXPOSITION AND THE NATIONAL FIBER OPTIC ENGINEERS CONFERENCE (OFC/NFOEC))

20 krad/s endless optical polarisation and phase control - Koch, B.; Noé, Reinhold; Mirvoda, V.; Sandel, D. (ELECTRONICS LETTERS)

An Ultralow Complexity Algorithm for Frame Synchronization and IQ Alignment in CO-OFDM Systems - Puntsri, K.; Jan, O.; Al-Bermani, A.; Woerdehoff, C.; Sandel, D.; Hussin, S.; Panhwar, M. F.; Noé, Reinhold; Rueckert, U. (2013 OPTICAL FIBER COMMUNICATION CONFERENCE AND EXPOSITION AND THE NATIONAL FIBER OPTIC ENGINEERS CONFERENCE (OFC/NFOEC))

20-Gb/s PDM-RZ-DPSK Transmission With 40 krad/s Endless Optical Polarization Tracking - Koch, Benjamin; Noé, Reinhold; Sandel, David; Mirvoda, Vitali; Omar, Jan; Puntsri, Kidsanapong (IEEE PHOTONICS TECHNOLOGY LETTERS)

ISI Tolerance of Cyclic Prefix Free Coherent Optical OFDM Communication systems - Puntsri, Kidsanapong; Jan, Omar; Al-Bermani, Ali; Woerdehoff, Christian; Sandel, David; Panhwar, Muhammad Fawad; Hussin, Saleh; Rueckert, Ulrich; Noé, Reinhold (2013 ITG Symposium Proceedings - Photonic Networks)

Analysis of Partial Pilot Filling Phase Noise Compensation for CO-OFDM Systems - Hussin, Saleh; Puntsri, Kidsanapong; Noé, Reinhold (IEEE Photonics Technology Letters)

20-Gb/s PDM-RZ-DPSK Transmission With 40 krad/s Endless Optical Polarization Tracking - Koch, Benjamin; Noé, Reinhold; Sandel, David; Mirvoda, Vitali; Omar, Jan; Puntsri, Kidsanapong (IEEE Photonics Technology Letters)

Lieder singen, Lieder schreiben: ‚Sechs deutsche Lieder‘ op. 14 von Josephine Lang und Reinhold Köstlin - Grotjahn, Rebecca (Liedersingen. Studien zur Aufführungsgeschichte des Liedes)

Höhere Tochter spielen. Musik, Gender, Bürgerlichkeit um 1900 - Grotjahn, Rebecca (Einsichten und Aussichten. Ein interdisziplinärer Auftakt)

‚Mein bessres Ich‘ – Schumanns Myrthen als Selbstbildnis des Künstlers - Grotjahn, Rebecca (Autorschaft – Genie – Geschlecht. Musikalische Schaffensprozesse von der frühen Neuzeit bis zur Gegenwart)

‚Precisely as sung by Her‘ – zur Mediengeschichte des Stars im 19. Jahrhundert - Grotjahn, Rebecca (ShePOP – Frauen. Macht. Musik!)

X-ray Spectroscopic Verification of the Active Species in Iron-Catalyzed Cross-Coupling Reactions - Schoch, Roland; Desens, Willi; Werner, Thomas; Bauer, Matthias (Chemistry - A European Journal)
Keywords: General Chemistry; Catalysis; Organic Chemistry

Experimental Investigations on the Induced Anisotropy of Mechanical Properties in Polycarbonate Films - Wibbeke, Andrea; Schöeppner, Volker; Mahnken, Rolf (ISRN Materials Science)
The prime aim of this paper is to investigate, with the help of experiments, the induced anisotropy of mechanical properties in polycarbonate films. It is known that a molecular orientation in polymer materials occurs through cold-forming. In this study, cold forming is performed at room temperature on a tensile testing machine. The polycarbonate films are examined in two phases. In the first phase, the specimen is loaded, while the prestrain is varied, and in the second, it is loaded, while the material direction is varied. The main findings are that the prestrain has virtually no influence on the anisotropy and that the material direction does exert a major influence. Furthermore, this paper summarizes comparisons of anisotropic characteristic data, maximum stresses, elasticity moduli and failure strain.

Parameter Identification in Continuum Mechanics: From Hand-Fitting to Stochastic Modelling - Mahnken, Rolf (The History of Theoretical, Material and Computational Mechanics - Mathematics Meets Mechanics and Engineering)

A multi-mechanism model for cutting simulations combining visco-plastic asymmetry and phase transformation - Mahnken, Rolf; Wolff, M.; Cheng, C. (International Journal of Solids and Structures)

Finite Deformation Plasticity with Void Growth and Asymmetric Compression-Tension Behavior - Mahnken, Rolf; Stein, E. (IUTAM Symposium on Computational Mechanics of Solid Materials at Large Strains)

Thermodynamic consistent modeling of polymer curing coupled to visco–elasticity at large strains - Mahnken, Rolf (International Journal of Solids and Structures)

Goal-oriented adaptive refinement for phase field modeling with finite elements - Mahnken, Rolf (International Journal for Numerical Methods in Engineering)

Simulation of strain-induced anisotropy for polymers with weighting functions - Mahnken, Rolf; Dammann, Christian (Archive of Applied Mechanics)

A Multi-Mechanism Model for Cutting Simulations Combining Visco-plastic Asymmetry and Phase Transformation - Cheng, Chun; Mahnken, Rolf; Uhlmann, Eckart; Ivanov, Ivan Mitkov (PAMM)

Eltern- und Familienbildung im Kindergarten. Zwischen gemeinsamer Erziehungsverantwortung, sozialer Teilhabe und frühkindlicher Entwicklungsförderung - Faas, Stefan; Landhäußer, Sandra (Konsens und Kontroversen. Sozialpädagogik und Pädagogik der frühen Kindheit im Dialog)
Thema der vorliegenden Publikation sind aktuelle Entwicklungen und Forschungen an der Schnittstelle zwischen Sozialpädagogik und Kindheitspädagogik. Der Wandel, den das Feld durch u.a. die Folgen des „PISA-Schocks“, die neue Thematisierung von Bildung im Elementarbereich, den U3-Ausbau, familienpolitische Entscheidungen und die Expansion von Studiengängen für Kindheitspädagogik erfährt, wird aus verschiedenen Perspektiven aufgegriffen und wissenschaftlich in zumeist inter- oder transdisziplinärer Weise unter die Lupe genommen. Herausgeberin ist die – seit 2011 unter erweiterter Bezeichnung agierende - „Sektion Sozialpädagogik und Pädagogik der frühen Kindheit“ der Deutschen Gesellschaft für Erziehungswissenschaft. Der Band ist das „Ergebnis eines Dialogs“ (S. 9) von Vertreter/innen der Sozialpädagogik und der Kindheitspädagogik. Er markiert damit einen Wendepunkt im Verhältnis der beiden Bereiche bzw. Teildisziplinen und ihrer entsprechenden Kommissionen innerhalb der DGfE, die Ende der 1990er Jahre unter dem Dach der „Sektion Sozialpädagogik“ vereint wurden und dort eher nebeneinander agierten. Den neuen Orientierungen des vorangegangenen Jahrzehnts Rechnung tragend, veranstalteten die beiden Kommissionen im Sommer 2011 in Erkner bei Berlin eine gemeinsame Tagung, aus der die Beiträge zum vorliegenden Band hervorgegangen sind und im Rahmen derer die Aufnahme der „Pädagogik der frühen Kindheit“ in den Sektionstitel beschlossen wurde. Damit ist der Band auch Ausdruck eines erneuten „Aufeinanderzugehens“, dessen weitere Entwicklung mit Spannung beobachtet werden kann.
Keywords: Erziehungswissenschaft | Soziale Arbeit | Sozialpädagogik | Kindheitsforschung | Kommission

Hydrophobic gold nanoparticles via silane conjugation: chemically and thermally robust nanoparticles as dopants for nematic liquid crystals - Mirzaei, Javad; Urbanski, Martin; Kitzerow, Heinz-Siegfried; Hegmann, Torsten (Philosophical Transactions of the Royal Society A: Mathematical, Physical and Engineering Sciences)
We examine for the first time how chemically and thermally stable gold nanoparticles (NPs), prepared by a silane conjugation approach, affect both the thermal and the electro-optical properties of a nematic liquid crystal (LC), when doped at concentrations ranging from 0.25 to 7.5 wt%. We find that the octadecylsilane-conjugated gold NPs stabilize both the enantiotropic nematic and the monotropic smectic-A phases of the LC host with a maximum stabilization of 2 ° C for the nematic and 3.5 ° C for the smectic-A phases for the mixture containing 1 wt% of the silanized particles. The same mixture shows the lowest values for the Fréedericksz transition threshold voltage and the highest value for the dielectric anisotropy. Generally, all NP-containing mixtures, except mixtures with NP concentrations exceeding 5 wt%, reduce the threshold voltage, increase the dielectric anisotropy and reduce both rise and decay time; the latter particularly at temperatures at least 10 ° C below the isotropic–nematic phase transition on cooling.
Keywords: General Physics and Astronomy; General Engineering; General Mathematics

Microresonator-enhanced electroluminescence of an organic light emitting diode based on a columnar liquid crystal - Vollbrecht, Joachim; Kasdorf, Olga; Quiring, Viktor; Suche, Hubertus; Bock, Harald; Kitzerow, Heinz-Siegfried (Applied Physics Letters)
Keywords: Physics and Astronomy (miscellaneous)

Limit transition between hypergeometric functions of type BC and type A - Rösler, Margit; Koornwinder, Tom; Voit, Michael (Compositio Mathematica)
Abstract Let ${F}_{BC} (λ , k; t)$ be the Heckman–Opdam hypergeometric function of type BC with multiplicities $k= ({k}_{1} , {k}_{2} , {k}_{3} )$ and weighted half-sum $ρ (k)$ of positive roots. We prove that ${F}_{BC} (λ + ρ (k), k; t)$ converges as ${k}_{1} + {k}_{2} → ∞ $ and ${k}_{1} / {k}_{2} → ∞ $ to a function of type A for $t\in { \mathbb{R} }^{n} $ and $λ \in { \mathbb{C} }^{n} $ . This limit is obtained from a corresponding result for Jacobi polynomials of type BC, which is proven for a slightly more general limit behavior of the multiplicities, using an explicit representation of Jacobi polynomials in terms of Jack polynomials. Our limits include limit transitions for the spherical functions of non-compact Grassmann manifolds over one of the fields $ \mathbb{F} = \mathbb{R} , \mathbb{C} , \mathbb{H} $ when the rank is fixed and the dimension tends to infinity. The limit functions turn out to be exactly the spherical functions of the corresponding infinite-dimensional Grassmann manifold in the sense of Olshanski.
Keywords: Algebra and Number Theory

Olshanski spherical functions for infinite dimensional motion groups of fixed rank - Rösler, Margit; Voit, Michael (Journal of Lie Theory 23)